2018
DOI: 10.1002/acm2.12485
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo and analytic modeling of an Elekta Infinity linac with Agility MLC: Investigating the significance of accurate model parameters for small radiation fields

Abstract: PurposeTo explain the deviation observed between measured and Monaco calculated dose profiles for a small field (i.e., alternating open‐closed MLC pattern). A Monte Carlo (MC) model of an Elekta Infinity linac with Agility MLC was created and validated against measurements. In addition, an analytic model which predicts the fluence at the isocenter plane was used to study the impact of multiple beam parameters on the accuracy of dose calculations for small fields.MethodsA detailed MC model of a 6 MV Elekta Infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…Alternatively, this result may be due to the use of Elekta linear accelerators, which have been suggested to display a wider focal spot in the crossplane direction relative to in-plane. 11,12 This would cause a wider cross-plane beam penumbra, increasing the number of pixels measured, and a correspondingly smaller pixel scale factor which is consistent with the study findings. Change in pixel scale factor with SSD followed a predictable linear trend, varying by 0.00025 mm/pixel for each millimeter error in SSD.…”
Section: Discussionsupporting
confidence: 87%
“…Alternatively, this result may be due to the use of Elekta linear accelerators, which have been suggested to display a wider focal spot in the crossplane direction relative to in-plane. 11,12 This would cause a wider cross-plane beam penumbra, increasing the number of pixels measured, and a correspondingly smaller pixel scale factor which is consistent with the study findings. Change in pixel scale factor with SSD followed a predictable linear trend, varying by 0.00025 mm/pixel for each millimeter error in SSD.…”
Section: Discussionsupporting
confidence: 87%
“…Based on the previous studies, MC simulation has been considered to be the most accurate tool to describe the underlying physical interactions between radiation and matter. EGSnrc MC Software has been successfully used in various dosimetry principles,[ 12 13 ] HVL evaluation of orthovoltage machine,[ 14 ] simulation of radiotherapy treatment units,[ 15 16 17 18 ] beam quality correction factor,[ 19 ] and so forth. Furthermore, previous studies have shown that MC can be used in the evaluation of X-rays transmission through some shielding materials,[ 11 ] evaluation of the attenuation coefficient of personal radiation shielding protective clothing,[ 20 ] determination of shielding properties of concrete,[ 21 ] shielding analysis,[ 22 ] and the simulation of X-ray room shielding in diagnostic radiology.…”
Section: Discussionmentioning
confidence: 99%
“…There have been previous groups to model Elekta's 160 leaf Agility collimator. [27][28][29] However, to the best of our knowledge, there is currently no model of Elekta's Versa HD linear accelerator that can be used for routine dose calculation on patients' CT datasets. We have developed a method for routine, independent patient dose calculations from treatment plans generated in a commercial TPS with our own Monte Carlo model.…”
Section: Introductionmentioning
confidence: 99%